SPATIAL DISTRIBUTION OF PALM SWAMP THROUGH SUPERVISED CLASSIFICATION OF SATELLITE IMAGES OF UCAYALI REGION, PERU - REVILLA CHAVEZ, Jorge (2020)
Palm swamps are ecosystems with a predominant presence of the palm Mauritia flexuosa, which provides important socio-economic and environmental benefits to the inhabitants of the Peruvian Amazon. The objective of this study is to determine the extent of palm swamp forest in the Ucayali region, Peru, through the supervised classification method of satellite images generated by the LANDSAT 8 Earth Observation satellite through the OLI-TIRS sensor, corresponding to Ucayali region in 2017. We visually interpreted the combination of bands 5 (Near Infrared (NIR), with wavelengths of 0.85 - 0.88 μm), 6 (Short Wave Infrared 1 (SWIR 1), with wavelengths of 1.57 - 1.65 μm) and 2 (Blue, with wavelengths of 0.45 - 0.51 μm) to obtain the map of palm swamp forest with an interpretation scale of 1:100 000 and a minimum mapping area of 5.00 ha. We determined a coverage of 65 120.04 ha of palm swamp forest in the Ucayali region. Identifying the location and net area of palm swamp forests in the Ucayali region will allow further understanding of their potential benefits, management and utilization of fruits, environmental services and also information for better management in the context of climate change.